Fotografía actual: expansiones, asincronías y promiscuidades - Cifuentes, Adolfo (2018)
The present work aims to replenish the relevance of photography, looking for the configurations that made it a promiscuous, expanded, paradoxical and omnipresent practice in the ways of relating, investigating and organizing the world. Thus, it provides us with ways to manage, disseminate and classify the universe through several authors. To map these expansions, four major strategies are proposed.